Climate sensitivity of shrub growth across the tundra biome - Myers-Smith, Isla H.; Elmendorf, Sarah C.; Beck, Pieter S. A.; Wilmking, Martin; Hallinger, Martin; Blok, Daan; Tape, Ken D.; Rayback, Shelly A.; Macias-Fauria, Marc; Forbes, Bruce C.; Speed, James D. M.; Boulanger-Lapointe, Noémie; et al. (Nature Climate Change, 2015)
Rapid climate warming in the tundra biome has been linked to increasing shrub dominance1–4. Shrub expansion can modify climate by altering surface albedo, energy and water balance, and permafrost2,5–8, yet the drivers of shrub growth remain poorly understood. Dendroecological data consisting of multi-decadal time series of annual shrub growth provide an underused resource to explore climate–growth relationships. Here, we analyse circumpolar data from 37 Arctic and alpine sites in 9 countries, including 25 species, and ⇠42,000 annual growth records from 1,821 individuals. Our analyses demonstrate that the sensitivity of shrub growth to climate was: (1) heterogeneous, with European sites showing greater summer temperature sensitivity than North American sites, and (2) higher at sites with greater soil moisture and for taller shrubs (for example, alders and willows) growing at their northern or upper elevational range edges. Across latitude, climate sensitivity of growth was greatest at the boundary between the Low and High Arctic, where permafrost is thawing4 and most of the global permafrost soil carbon pool is stored9. The observed variation in climate–shrub growth relationships should be incorporated into Earth system models to improve future projections of climate change impacts across the tundra biome.